1995
DOI: 10.1515/hfsg.1995.49.6.548
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Adsorption Thermodynamics of Chemically Modified Wood

Abstract: The isotherms for untreated and chemically modified wood specimens were analyzed using the Hailwood-Horrobin equation. The enthalpy (ΔΗ), entropy (AS) and free energy (AG) changes during moisture adsorption were estimated. The AH, AS and AG values of untreated wood were compared with those found in literature as well as those of specimens treated with formaldehyde (formalization), acetic anhydride, glyoxal, glutaraldehyde and dimethylol dihydroxy ethyleneurea (DMDHEU). The AH of the untreated specimen was almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 10 publications
4
30
0
Order By: Relevance
“…Of the different methods for generating specific RH levels detailed above, one of the most common methods is by saturated salt solutions (Ammer 1963b;Eriksson and Noren 1965;Forster 1998;Higgins 1957;Nearn 1955;Papadopoulos and Hill 2003;Wangaard and Granados 1967;Yasuda et al 1995) since they are relatively simple to use and cover a wide range of RH levels (see, for example, Greenspan 1977) for solutions in the range 3-98% RH. Their use limits, however, which RH levels can be achieved.…”
Section: Gravimetric Techniquesmentioning
confidence: 99%
“…Of the different methods for generating specific RH levels detailed above, one of the most common methods is by saturated salt solutions (Ammer 1963b;Eriksson and Noren 1965;Forster 1998;Higgins 1957;Nearn 1955;Papadopoulos and Hill 2003;Wangaard and Granados 1967;Yasuda et al 1995) since they are relatively simple to use and cover a wide range of RH levels (see, for example, Greenspan 1977) for solutions in the range 3-98% RH. Their use limits, however, which RH levels can be achieved.…”
Section: Gravimetric Techniquesmentioning
confidence: 99%
“…(5) is given incorrectly by Yasuda et al (1995). From the above relationships, the values K 1 , K 2 and W can be derived as shown in Eqs.…”
Section: Figurementioning
confidence: 99%
“…Popper and Bariska (1972) reported H-H polylayer and monolayer isotherm data for acetylated fir. Yasuda et al (1995) (2005) subsequently found that the (H-H) model gave the best fit to experimental data. However, none of these studies reported the data in terms of EMC R .…”
Section: Introductionmentioning
confidence: 99%
“…If they are compared point by point, all the coefficients show values which agree with this affirmation. Despite the fact that at point 11.17% of the LiCl salt the old wood has a higher hysteresis coefficient than in the new wood (1.00 as opposed to 0.86), it was considered that this point should be removed as there was a possibility that entropy peaks may have an influence at low humidities [41]. Kadita et al [17] speculated that these peaks were due to the fact that the hydroxyl groups in the amorphous region form bonds in the wood when the wood is oven-dried.…”
Section: H Emc a Emc D ---------------=mentioning
confidence: 99%